A single dose of inactivated influenza virus vaccine expressing COBRA hemagglutinin elicits broadly-reactive and long-lasting protection - Hua Shi; Xiaojian Zhang; Ted M. Ross (PLoS ONE, 2025)
Influenza virus infections present a pervasive global health concern resulting in millions of hospitalizations and thousands of fatalities annually. To address the influenza antigenic variation, the computationally optimized broadly reactive antigen (COBRA) methodology was used to design influenza hemagglutinin (HA) or neuraminidase (NA) for universal influenza vaccine candidates. In this study, whole inactivated virus (WIV) or split inactivated virus (SIV) vaccine formulations expressing either the H1 COBRA HA or H3 COBRA HA were formulated with or without an adjuvant and tested in ferrets with pre-existing anti-influenza immunity. A single dose of the COBRA-WIV vaccine elicited a robust and broadly reactive antibody response against H1N1 and H3N2 influenza viruses. In contrast, the COBRA-SIV elicited antibodies that recognized fewer viruses, but with R-DOATP, its specificity was expanded. Vaccinated ferrets were protected against morbidity and mortality following challenge with A/California/07/2009 at 14 weeks post-vaccination with reduced viral shedding post-infection compared to the naïve ferrets. However, the COBRA-IIVs did not block the viral transmission to naïve ferrets. The contact infection induced less severe disease and delayed viral shedding than direct infection. Overall, the COBRA HA WIV or the COBRA HA SIV plus R-DOTAP elicited broadly reactive antibodies with long-term protection against viral challenge and reduced viral transmission following a single dose of vaccine in ferrets pre-immune to historical H1N1 and H3N2 influenza viruses. IMPORTANCE The goal of the next-generation influenza vaccine is to provide broadly reactive protection against various drifted influenza strains. With the previous studies evaluating the COBRA HA-based vaccines, the breadth of antibody activities was confirmed following two or three vaccinations. However, for the commercial influenza vaccine, only one shot is required. In this study, only one shot was administrated to the pre-immune ferrets and the COBRA-WIV efficiently elicited broadly reactive antibodies and long-lasting protection against the pdm09 strain. Moreover, this study showed that different infection methods can lead to different disease severity, which emphasizes the significance of the model selection. The infection was conducted 14 weeks post-vaccination to evaluate the long-term protection elicited by only one vaccination. This is the first longevity study describing the immune responses elicited by COBRA-IIVs in ferrets and provides promising results for the potential clinical utilization.